Investigating Security Awareness and Incident Reporting levels at Mbarara University of Science and Technology - Mbonimpa, Thomas; Richard, Ntwari; Innocent, Muhereza J.; Priscilla, Muheki (CV. Literasi Indonesia, 2024)
Higher learning institutions confront heightened cyber threats due to the value of their data, necessitating a robust security culture. In addition to cyber threats, various security incidents cause danger to devices and personal belongings on campuses. Security incidents present a substantial challenge to academic institutions, especially higher education, where their occurrence is notably prevalent. These incidents encompass a broad spectrum, including thefts, data breaches, malware attacks, and other breaches in physical security. Addressing security incidents necessitates critical strategies involving educating and raising awareness among the academic and surrounding communities. In this study, we aimed to investigate the security awareness levels of students at Mbarara University of Science and Technology and establish their incident reporting attitudes and levels. We used a quantitative research method and conducted different statistical tests. The findings indicate that 50% of the participants had not had any security awareness training, indicating a very big gap in the security culture at this institution. Although some of the students indicated their awareness of security threats, the percentage who showed a lack of awareness or a noncommittal response suggests that there is a very big need for security awareness strategies. Additionally, about 60% of the students showed their will to report security threats which implies that they can be vigilant about their and the institutional security. Based on these findings we recommend continuous training programs for students to increase their levels of awareness and incident reporting and consequently develop an institutional security culture.